Rancang Bangun Aplikasi Pemesanan Tiket Bus Online (BeTik Bus) Berbasis Website - Gregorius Aryo Prasojo; Rezza Pana Kontesta (Journal of Information Technology, 2023)
Buses are transportation that is still the main choice of people in areas that are easy to reach. By buying tickets through a bus agent, people can enjoy bus services. However, in the transaction process, people carry out their transactions manually, this method is still less effective and efficient. Through the website-based BeTik Bus application it can make it easier to buy bus tickets, people do not need to spend time and effort to order tickets, because through the website-based BeTik Bus application the user or users can buy tickets faster and more freely. This application also has a ticket printing feature which is useful for making it easier for prospective buyers to get non-physical evidence of tickets that have been ordered and validated by the admin, so that the BeTik Bus application design aims to help the community, especially people in border areas. The BeTik Bus application uses the waterfall method. Based on research that has been carried out, the design of the BeTik Bus application can be used by the community for online bus ordering needs and this application will later be developed in the Bengkayang district because it is strategically close to the Indonesia-Malaysia border which is a point of community mobility.